Abortions in the eastern macro-region of Maranhão: socioeconomic and clinical factors (Research, Society and Development, 2021)
This article aims to analyze the situation of abortions in the eastern macro-region of Maranhão and characterize the socioeconomic and demographic profile of the data in the period from 2010 to 2018. A descriptive population-based time series study was carried out that described the scenario of abortion using public data from information systems in Brazil – DATASUS (information from the Unified Health System (SUS)) and SIH (Hospital Hospitalization System). The evidence from the present research suggests that abortion in the macro-region under study is more prevalent in the municipality of Timon, corresponding to 19.91% of fetal deaths, in young women aged 15 to 19 years and with low or medium education, having a single-type pregnancy and type of vaginal delivery with 83.11%. There is also a prevalence of deaths related to maternal factors, equivalent to 39.82% of deaths and according to the category of the International Classification of Diseases ICD-10 due to intrauterine hypoxia with 29.87%. It is also observed the presence of many ignored cases, reflecting the importance of completely filling out hospital records, thus, this research is dedicated to assisting in the protection, prevention and promotion of the health of women and of the newborn.